Analyses on the technical efficiency of small scale rubber production in the selected areas in North Cotabato - Balaba, Rhezalyn S.
Rubber tree (Hevea brasiliensis) was already introduced and become a valuable crop since the 20th century. Throughout the years, the demand and supply for rubber is increasing. However, the Philippines seems to lag behind the other rubber producing countries in the world. The Data Envelopment Analysis (DEA) was performed using the primary data gathered from the field interviews with 100 rubber farmers in the six selected areas in North Cotabato. The DEA analysis used the volume of production per hectare as the output and the materials total labor and farm size as the inputs. All the variables were based on a monthly data. The study also employed Tobit Regression Analysis. In the analysis the dependent variable used are the Technical Efficiency scores with the independent variables, total labor, cost of materials, farm size, tenure, transport cost and age of rubber trees. The results of the study showed that farmers in the selected areas are not technically efficient in rubber farming. The DEA showed that in the Constant Returns to Scale Assumption only 2 out of 100 farms have a score 1.00, means that among the 100 farms in the selected areas only 2 are technically efficient. The Variables returns to scale assumption however showed that 24 out of 100 farms in the chosen areas in North Cotabato got a score of 1.00 and were technically efficient. It was also found out that Arakan was the most technically inefficient municipality among six municipalities. Among the six variables; total labor, cost of materials, farm size and transportation cost significantly affect the performance of the farms.